Tell Bapska and the Problem of LN Chronology in E Croatia - Burić, Marcel (2011)
The topic of the presentation were problems regarding low number of absolute 14C dates and their distribution throughought Eastern Croatia. Tell Bapska was introduced as the contact zone between south Transdanubian area and the core of the Late Neolithic Vinca Culture.
Projekt MZOS
ENG